Spectroscopic characteristics of Er3+ in the two crystallographic sites of Gd2SiO5 - De Camargo, A. S S [UNESP]; Davolos, Marian Rosaly [UNESP]; Nunes, L. A O (IOP Publishing, 2002)
Gd2SiO5 is among the interesting and suitable hosts for Er3+ which find extensive applications in the infrared, visible and ultraviolet spectral regions. In order to investigate its potentialities, a prior study of the spectroscopic behaviour of Er3+ substituting for Gd3+ ions in the two crystallographic sites of the host was performed. Absorption, excitation, site-selective emission and time-resolved spectroscopies were employed in the visible spectral region to study transitions between excited 4S3/2 and ground 4I15/2 states. These levels multiplets were attributed to each site separately, and their corresponding 4S3/2 lifetimes (1.8 ± 0.1 μs for site 1 and 3.2 ± 0.1 μs for site 2) were determined.
Keywords: Absorption; Crystallography; Erbium; Ground state; Infrared spectroscopy; Scintillation; Ultraviolet spectroscopy; Time-resolved spectroscopies; Gadolinium compounds